2010
DOI: 10.1590/s0037-86822010000600004
|View full text |Cite
|
Sign up to set email alerts
|

Antituberculosis drug-induced hepatotoxicity: a comparison between patients with and without human immunodeficiency virus seropositivity

Abstract: Introduction:The prevalence and risk factors for rifampin, isoniazid and pyrazinamide hepatotoxicity were evaluated in HIV-infected subjects and controls. Methods: Patients with tuberculosis (30 HIV positive and 132 HIV negative), aged between 18 and 80 years-old, admitted to hospital in Brazil, from 2005 to 2007, were selected for this investigation. Three definitions of hepatotoxicity were used: I) a 3-fold increase in the lower limit of normal for alanine-aminotransferase (ALT); II) a 3-fold increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…The prevalence of elevated ALT (13%) found in our study is lower than that reported among pre‐ART HIV‐infected individuals in Europe and North America, where rates vary between 19 and 29%, but similar to the findings of studies from Africa . In a multinational study of HIV‐infected patients in Kenya, Zambia and Thailand, baseline ALT > 40 IU/L was present in about 14% of 812 HIV‐infected patients .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The prevalence of elevated ALT (13%) found in our study is lower than that reported among pre‐ART HIV‐infected individuals in Europe and North America, where rates vary between 19 and 29%, but similar to the findings of studies from Africa . In a multinational study of HIV‐infected patients in Kenya, Zambia and Thailand, baseline ALT > 40 IU/L was present in about 14% of 812 HIV‐infected patients .…”
Section: Discussionsupporting
confidence: 80%
“…There are several reasons for this difference. First, in the studies from Europe and North/South America, male patients represented between 63 and 94% of the study population, whereas in our study female patients accounted for 71% of the study population . Secondly, an inverse relationship between Black ethnicity and chronic ALT elevation has been reported in several studies of HIV‐infected patients .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The recommended regimen in this population is isoniazid, pyrazinamide and ethambutol with moxifloxacin or levofloxacin [105].…”
Section: Special Situationsmentioning
confidence: 99%